Obesity and overweight in beliefs and attitudes of residents an urban Community from the Sociology of Health - Sifuentes León, Eudosio H. (2019)
Obesity and overweight are problems of malnutrition and public health in the communities and societies of the current era. Stopping and reducing them are immediate objectives of development, which not everyone assumes, especially those affected by their behavior and mentality, which deserves to be known. The study explores the beliefs and attitudes of residents of an urban community, against obesity and overweight, applying a mixed approach, qualitative observational in the first part and quantitative, descriptive, probabilistic by conglomerates, in the second. 240 inhabitants were surveyed, men and women from 18 to 70 years old; and 2456 people of all ages were observed. The analysis triangulates the information collected through surveys, interviews and observations. Individual and collective experiences were very unique in the processes of socialization, nutrition and social mobility; opportunities to incorporate elements of local, modern and traditional cultures; access to mass media and information technologies with possibilities of assimilating patterns of behavior, consumption, tastes and practices of the global society. Some residents, with extra kilos did not worry about their weight; others, seemed happy to have «chubby» children, who considered them «normal», with «good health» and above all to look like or have «the look of Limeños» and not of provincials, much less of «serranos»; what apparently allowed them to see themselves, in the local hierarchy, with more status and in a higher stratum than their neighbors.